Does labor diversity cause agglomeration in Japan?: an NEG approach with a covariance structure analysis - Ryusuke Ihara; Shizu Yamamoto (European Regional Science Association (ERSA), 2012)
Using a simplified NEG model, we investigates the relation between labor diversity and agglomeration. In the theoretical part, we assume the following two-region model. Homogenous consumption goods are produced using a constant returns technology with homogenous capital and heterogenous workers. The production function exhibits increasing returns to scale in labor diversity. Capital is freely mobile between the regions, while workers are immobile but can commute to the other region by paying the commuting cost. Considering the circular causation in this model, the backward linkage (i.e. agglomeration caused by labor demand) implies the agglomeration of capital leads workers to concentrate. The forward linkage (i.e. agglomeration caused by labor supply) implies the increase in the number of workers enhances labor diversity and causes agglomeration of capital. The theoretical result is summarized as follows. When interregional commuting cost is sufficiently low, workers tend to choose their jobs in the region with a larger share of capital. Furthermore, the inflow of commuting workers increases the degree of labor diversity in the labor receiving region, and causes agglomeration of capital. In the empirical part, we confirm the theoretical results by covariance structure analysis with Japanese prefectural datas. We construct path diagrams describing the above backward and forward linkages. In order to measure the latent factor of labor diversity, we use following six indices: newspaper subscription, car registration, votes share in national election, foreign travel, white-collar share, and interregional commute. As an empirical result, we reveal the existence of the circular causation in Japan. Concretely, on the backward linkage, capital agglomeration (the number of firms) has a significant and positive indirect effect on labor agglomeration (the number of workers) through the wage income of workers, as well as a direct effect on labor agglomeration. The forward linkage is also positive and significant. Labor agglomeration significantly enhances the labor diversity, and the labor diversity raises capital reward (firmsf profit) and leads capital (firms) to agglomerate. Besides, the labor diversity is strongly and significantly influenced by the indices of the car registration, the foreign travel, and the white-collar share. The empirical analysis in Japan supports the theoretical result that labor diversity causes agglomeration through the circular causation.
Keywords: R11; R12; J61; 330; labor heterogeneity; New economic geography; circular causation; covariance structure analysis